Epigenetics and Vascular Senescence–Potential New Therapeutic Targets? - Ding, Qian; Shao, Chunhong; Rose, Peter; Zhu, Yi Zhun (Frontiers in Pharmacology, 2020)
Epigenetics is defined as the heritable alterations of gene expression without changes to the coding sequence of DNA. These alterations are mediated by processes including DNA methylation, histone modifications, and non-coding RNAs mechanisms. Vascular aging consists of both structural and functional changes in the vasculature including pathological processes that drive progression such as vascular cell senescence, inflammation, oxidation stress, and calcification. As humans age, these pathological conditions gradually accumulate, driven by epigenetic alterations, and are linked to various aging-related diseases. The development of drugs targeting a spectrum of epigenetic processes therefore offers novel treatment strategies for the targeting of age-related diseases. In our previous studies, we identified HDAC4, JMJD3, Fra-1, and GATA4 as potential pharmacological targets for regulating vascular inflammation, injury, and senescence.